Operational uptime as performance-based measure of natural ventilation in an open car park - Miechówka, Bartosz; Węgrzyński, Wojciech; Jamińska-Gadomska, Paulina; Krajewski, Grzegorz (Instal, 2025)
192 CFD simulations of an open car park fire under wind conditions were conducted to assess the efficiency of natural ventilation. In the majority of considered cases, natural ventilation was ineffective. The influence of wind direction on ventilation performance was observed. Using historical wind data, the percentage of time during which the outcomes were acceptable was estimated. This value was termed operational uptime and amounted to 87.62% for a fire with a heat release rate of 1.4 MW; 40.30% for 4.0 MW; 36.39% for 6.0 MW; and 14.24% for 8.8 MW.